A kinestatic model for the three-dimensional static analysis of long combination vehicles - Moreno Contreras, Gonzalo Guillermo (2017)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro Tecnológico, Programa de Pós-Graduação em Engenharia Mecânica, Florianópolis, 2017.